ANALISIS MANAJEMEN KEUANGAN DESA DALAM MENINGKATKAN EFEKTIFITAS PELAKSANAAN PROGRAM PEMBANGUNAN DI DESA TASSESE KABUPATEN GOWA - Firmansyah Firmansyah; Aulia Aulia (Jurnal Ilmu Manajemen Profitability, 2020)
This study aims to determine and analyze Village Financial Management in Increasing the Effectiveness of the Implementation of Development Programs in Tassese Village, Gowa Regency. This type of research used a quantitative descriptive approach. The data used are village income budget in 2016, 2017,2018. The calculation technique used in the study is the effectiveness ratio  analysis. The results of the analysis though the calculation of the 2016 PAD effectiveness ratio income by 29% then the income is said to be ineffective and in 2017 the amount of revenue increased by 100% then the income is said to be effective, while in 2018 the amount of revenue decreased by 99% then the income is said to be quite effective. Financial analysis using the effectiveness fluctuation of PAD. Thus, it can be said that financial management through the effectiveness ratio helps planning and implementing development programs.